Inadequate Quality Research Outputs from Homoeopathic Colleges in India: Why? (Homoeopathy for All, 2025)
There are about 103 undergraduate and 57  postgraduate homoeopathic medical colleges  in India, permitted by National Council for  Homoeopathy (NCH), for admission during  the sessions 2024-25 & 2025-26. Having the  largest infrastructure in terms of colleges,  in comparison to other countries, their  contributions in the field of research are not so  much encouraging. If we meticulously analyse  different factors behind such inadequate  research outputs, the following issues will  generally come to our minds,
Keywords: undergraduate; postgraduate; homoeopathic; permitted; National Council